Malaysian university students' attitudes to academic dishonesty and business ethics - Ahmad, Zauwiyah; Simun, Maimun; Mohammad, Junaini (ROUTLEDGE JOURNALS, 2008)
Academic dishonesty is believed to have predictive ability for subsequent behaviours in the workplace. This study adds to the literature by investigating Malaysian business students' attitudes to academic dishonesty and their attitudes to ethics issues in business. This study also explores the association between these two constructs. The form of academic dishonesty being investigated here is related to assignments, quizzes, and examinations. Employing data collected from 153 business students from different academic years, this exploratory study concludes that business students may have found that some level of dishonesty is acceptable in some academic settings as well as in business settings. The study's outcomes highlight the possibility of using students' attitudes to academic dishonesty to explain their attitudes to ethics in business contexts. The findings of this study, to a certain extent, indicate that years spent in business education might contribute to such unfavourable attitudes. This exploratory study also draws attention to several issues related to the teaching of ethics within business education.